Computational analysis of insect impingement patterns on wind turbine blades. Issue 3 (15th April 2015) - Wilcox, Benjamin; White, Edward
Abstract: Wind turbines experience significant power loss due to insect contamination on the blades. In order to estimate power losses, computational fluid dynamics software or empirical models are used to compute drag increases due to roughness‐induced boundary‐layer transition. These models require knowledge of the expected levels and location of insect contamination on the blade surface. This is generally unknown, making power loss predictions unreliable. The present study develops a computer simulation to predict this information and uses this tool to simulate insect impingement for a variety of turbine operating conditions. The simulation code combines an invsicid panel method with a Lagrangian insect particle simulation module to first solve for the turbine velocity field and then track insect paths through this field. The effects of blade thickness, angle of attack and insect size are studied for 2D airfoil sections. The simulations show that increasing blade thickness leads to a larger chordwise extent of insect impingement yet lower maximum levels of contamination. Increasing insect mass is also found to increase the chordwise extent of impingement. These results are consistent with previous wind tunnel results and theoretical predictions. The model is then applied to a representative 5‐MW turbine model to determine spanwise variation in contamination. Results agree qualitatively with field observation, suggesting that this technique may be used in the future to more accurately predict power losses on turbines. Copyright © 2015 John Wiley & Sons, Ltd.